(untitled) (Ecological Perspective, 2025)
A sustainable urban plan needs to consider human beings and the natural environment in which they live together. The distribution and development of urban green areas have an important role in the formation of a healthy urban environment. The rapid urbanization that occurred in the world with industrialization gained momentum in Turkey in the 20th century. In this process, important environmental problems have emerged over time in Şanliurfa, which has become an unplanned urbanization as a result of the need for settlement that emerged with the effect of migration from rural to urban areas, as in many cities. In this study, the effects of ecological approaches, which have emerged in recent years to combat environmental problems worldwide, on the city of Şanliurfa are examined through the recently developed Veysel Karani and Karşıyaka neighborhoods of Haliliye District. The data obtained from the field study were evaluated and it was determined that these two neighborhoods, which are still developing, are far from being ecosystems aiming at the continuity of species and are only human-oriented planned areas. Suggestions have been developed for these two areas to evolve into ecological settlements in the ongoing development process.